A matriz do poder totalitário: reflexões sobre a Alemanha nacional-socialista - Lévy, Gilbert Isidore (2008)
This research encompasses two parts: a matrix and the manifestations of the totalitarian Power. The matrix is analyzed on its cultural, social and political aspects, focusing on the National Socialist German totalitarian experience. The cultural matrix puts into evidence a Conservative Revolucionary movement and the influence of the nihilist culture on national Socialist speech, from the studies of Louis Dupeux and of Léo Strauss. The social matrix is based on the work developed by George Mosse regarding the social impact of the 1st World War on the civilian society, on which he denominates the brutalization of the German society. The political matrix seeks to unveil the essence of the totalitarian Power. It is based on the observations of three important authors: Claude Lefort, who points out that the roots of the totalitarianism are in the ambiguities and imperfections of the democracy itself, with the concept of democratic indetermination. Aléxis de Tocqueville, with the tyranny of the majority, an expression that configures a political situation in which there is no counterweight to limit the excesses of power, nor protection to grant the natural rights of the minority, and, finally, Giorgio Agamben, starting from a study of the dialectical relation between the sovereign Power and the bare life, points to the danger coming from the vitalist political conception, denominated biopolitics by Foucault, when the same seeks the development of the vital potential of a nation. From the three aspects studied, in the political matrix the more conclusive explanations for the emergence of the totalitarianism is found. The democratic indetermination and the life´s politization are two subjects that stand out in this matrix, due to the relevance of the explanations from Lefort and Agamben, as the preponderant factors on the emergence of totalitarian dynamics. In the second part, the purpose is to demonstrate how this dynamic was expressed in Germany, during the National Socialist regime. For that, the following manifestations of the totalitarian power were outlined: völkische identity, Total State, Total Mobilization and Total war, illuminated by the observations from Bernard Bruneteau, to end with a picture of the totalitarian evil